Non-destructive analysis of the content of mineral components of chicory to increase its environmental safety - Popova, Inna; Palamarchuk, Igor; Zheplinska, Mariia; Mushtruk, Mikhailo; Vasyliv, Volodymyr (My University, 2024)
The content of heavy metals both in plants and in soils for growing agricultural crops steadily changes the state of ecological safety of the corresponding biocenosis. An increased amount of trace elements and compounds of heavy metals causes metabolic disorders in plant tissues. As a result, there is an accumulation of toxic elements in the crops, which disrupts the iocenosis in the system for both farm animals and humans. Therefore, the contamination of plant raw materials, in particular chicory, for the food industry with ions of heavy and toxic metals is a significant environmental problem

Вміст важких металів як у рослинах, так і в ґрунтах вирощування сільськогосподарських культур неухильно змінює стан екологічної безпеки відповідного біоценозу. Підвищена кількість мікроелементів і сполук важких металів викликає порушення обміну речовин у рослинних тканинах. В результаті в посівах відбувається накопичення токсичних елементів, що порушує , біоценоз в системі як для сільськогосподарських тварин, так і для людини. Тому забруднення рослинної сировини, зокрема цикорію, для харчової промисловості іонами важких і токсичних металів є значною екологічною проблемою
Keywords: chicory; біоценоз; biocenosis; цикорій; кафедра харчової хімії